#### Answer

$\displaystyle \frac{x^{2}+5x+25}{x+5} $

#### Work Step by Step

Simplifying Rational Expressions
1. Factor the numerator and the denominator completely.
2. Divide both the numerator and the denominator by any common factors.
---
Numerator: recognize a difference of cubes:
$x^{3}-5^{3}=(x-5)(x^{2}+5x+25)$
Denominator: recognize a difference of squares
$x^{2}-5^{2}=(x+5)(x-5)$
Expression = $\displaystyle \frac{(x-5)(x^{2}+5x+25)}{(x+5)(x-5)}$
... divide both with the common factor: $(x-5)$
Expression = $\displaystyle \frac{x^{2}+5x+25}{x+5} $